Black Sunlight - Dambudzo Marechera (1952-87) (Hainemann, 1980)
Dystopia set in a future of constant war. A play, Black Sunlight, by the Zimbabwean author and playwright Petina Gappah (b. 1971) based on Marechera’s life, premiered in Harare, Zimbabwe, in November 2020. The first act can be found in The Johannesburg Review of Books 4.7 (August 2020). [The JRB Exclusive] Read the first act of Petina Gappah’s new Dambudzo Marechera play, Black Sunlight – The Johannesburg Review of Books.
Originated in part from a manuscript published as “Black Insider.” In his Black Insider. Comp. and ed. Flora Veit-Wild. Harare, Zimbabwe: Baobab Books, 1990), 23-115.  Rpt. (London: Lawrence & Wishart, 1992), 33-154. U.S. ed. (Trenton, NJ: Africa World Books, 1999), 23-115.
Keywords: Male author; Zimbabwean author